The effect of herbs on the microbiological stability and nutritional quality of pariser - Posgay, Miklós; Lakatos, Erika; Kapcsándi, Viktória (Acta Agraria Debreceniensis, 2020)
The purpose of this study was to evaluate the functional properties of dried herbs (Thymus vulgaris L., Origanum vulgare L., Salvia officinalis L.) to improve the quality characteristics and microbiological stability of Hungarian meat product, pariser. The addition of herbs did not affect the microbial properties of the product. According to the Decree No. 4 of 1998 of the Ministry of Health, pariser can be considered safe. The nutritional quality of the different forms of pariser was also acceptable. However, the addition of oregano, sage and thyme changed the flavor characteristics of the parisers and the higher meat content would increase the final price of the product.